Dispositivos móveis e acessibilidade: um estudo sobre o uso do Flipboard por pessoas com deficiências visuais - Burgos, Leonardo Alves Siqueira (2018)
This research analyzes the functionality and usability of the Flipboard news application specifically for the visually impaired public, in two aspects of initial appeal: the employability of the design and the search for consumer confidence from the reinforcement of importance of the credibility between the news selected for it by the application. In order to reach the objective, an analysis was made of the application's functions, including accessibility, punctuated from theoretical concepts and practical concepts, among them the application of observation of the use of the same by people with visual deficiencies. It has been discovered that in addition to the incessant search for the exact selection of news for each consumer in a personalized way from computer algorithms, there is a latent concern with the elimination of news that may be untrue and with the design employed in all stages of the process of news reading. One of the questions developed here is: does the functionality of this design also apply to the visually impaired public? It has been possible to identify that Flipboard is a business model focused on the premium consumer and that somehow reconfigures the mode of production and dissemination of news, based until then on the industrial model, but does not present itself as a completely accessible product for people with visual impairments.